(untitled) (Stavební obzor - Civil Engineering Journal, 2023)
The prestressed ducts of prestressed concrete continuous girder bridges are usually three-dimensionally distributed and long in length. The control of prestress loss during construction is very important. In order to ensure the effect of prestress tensioning, the test and analysis of friction parameters of prestressed ducts are particularly important. Based on the tension process of a prestressed concrete continuous beam bridge, the initial tension stress, loading time and channel friction parameters of the prestressed concrete continuous beam bridge are tested by field tests. Combined with the measured friction parameters, the finite element software Midas / Civil is used to analyse the influence of friction parameters on the mechanical properties of prestressed concrete continuous beam bridge. The results show that when the prestressed steel with bending angle not more than 40° and length not more than 70 m is stretched, the initial tension stress is suggested to be set as 20 % of the tension control force and the loading time is 5 min. The measured tunnel friction parameters are larger than the standard value, and the tension control force should be adjusted during the formal tension construction；The deflection of the key section of the main beam increases with the increase of the friction parameters, and the roof stress decreases with the increase of the friction parameters. The change of channel deviation coefficient has a greater impact on the deflection and roof stress than the change of friction coefficient.